548 Oncological outcome of sentinel lymph node mapping or comprehensive surgical staging in patients with node-negative intermediate-risk endometrial cancer. (4th December 2020) - Siegenthaler, Franziska; Imboden, Sara; Mueller, Michael
Abstract : Introduction/Background: The role of lymphadenectomy in surgical staging for endometrial cancer remains controversial. The standard of care – consisting of a pelvic and para-aortic lymphadenectomy (LND) – has failed to show survival advantage while leading to an increased peri- and postoperative morbidity. Sentinel lymph node (SLN) mapping has gained popularity, offering a compromise between no nodal staging and complete LND. Multiple studies have demonstrated high detecection rates and negative predictive values of SLN mapping with near-infrared fluorescence imaging and indocyanine green (ICG) in endometrial cancer. However, the literature contains limited data on its safety and oncological outcomes. Aim of this study is to evaluate the oncological outcome of SLN mapping in patients with intermediate-risk endometrial cancer. Methodology: In a retrospective, single-center study, we investigated the oncological outcome of patients with stage I intermediate-risk endometrial cancer who underwent surgical staging at our institution between February 2013 and July 2020. Results: Out of a total number of 306 patients with endometrial cancer, 57 patients were diagnosed with node-negative intermediate-risk endometroid endometrial cancer (FIGO IA grade 3, FIGO IB grade 1 or 2). All patients were treated with laparoscopic hysterectomy and bilateral salpingo-oophorectomy with ICG SLN mapping. 31 patients additionally underwent comprehensive surgical staging (four systematic pelvic lymphadenectomies and 27 pelvic and para-aortic lymphadenectomies, LND group). Mean follow up time was 38.0 months. Adjuvant treatment consisted of vaginal brachytherapy in 49 patients, additional chemotherapy in four patients and no adjuvant treatment in eight patients. Between the two cohorts, there were no differences in age or BMI. The mean number of lymph nodes removed (4.04 vs. 45.5), the duration of the surgical procedure (131.3 vs. 287 minutes) as well as the intraoperative blood loss (101.9 vs. 258.1 ml) were significantly higher in the LND group (p=0.000, 0.000 and 0.026, respectively). Recurrence rates (7.7% SLN, 9.7% LND, p=0.585) and death due to disease (3.8% SLN, 3.2% LND, p=0.709) were similar between the two groups. Further on, there was no statistically significant difference in overall and recurrence free survival for patients with SLN mapping only compared to the LND cohort (p=0.541 and 0.480, respectively). Conclusion: In our cohort, the use of ICG SLN mapping alone did not impair oncological outcome compared to a complete lymphadenectomy. It therefore might provide an efficient alternative of nodal staging with less morbidity in intermediate-risk endometrial cancer patients. However, prospective studies on larger numbers of patients are needed to confirm our findings. Disclosures: No disclosures.